Molecular simulation of the effect of plasma modification on the microscopic properties of polyimide - Ding, Can; Chen, Chen; Yuan, Zhao; Chen, LiXue (Frontiers in Materials, 2022)
Polyimide is often used as the insulating material of the repulsion coil, which needs to withstand the collision of the fast repulsion mechanism in high-speed motion, temperature rise and high voltage. The polyimide molecular model was established in this paper. The external electric field was applied to the model through the semi-empirical method to calculate the total molecular energy, dipole moment, molecular orbital energy, and energy gap of polyimide. It was found that the total molecular energy of plasma modified polyimide was lower, the energy gap was smaller, and the corresponding molecular properties were more stable. Then the cell models of ordinary polyimide and plasma modified polyimide were established by molecular dynamics simulation. The effects of plasma modification on the micro properties of polyimide were studied and compared. The free volume, mean square displacement, cohesive energy density, mechanical properties, and relative dielectric constant of polyimide models with different modified ratios were calculated. The results show that the introduction of polar groups through plasma modification can inhibit the movement of the polyimide molecular chain and improve the thermal stability of polyimide system. The mechanical properties of polyimide are also improved due to plasma modification, and the elastic modulus is the largest when the modification rate is 20%. At the same time, the relative dielectric constant of polyimide increases with the increase of the modification rate.